Union Decline: Lessons from Alberta - Reshef, Yonatan; Murray, Alan (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1991)
This paper tests whether an inconsistency exists between unions' industrial relations philosophies and their abilities to secure real wage gains. One economic measure and two attitudinal measures are related to union membership. The influence of these measures on both the likelihood that a person is a union member and union membership's impact upon these measures are simultaneously estimated. The implications of the results for private-sector union decline in Canada are then discussed.